Spore on-the-job - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
During the quieter periods of our vaccination programmes, I read Spore from cover to cover. One recent issue had an article about pasture management; I was able to discuss it straight away with the next group of herders to come along. N Tio...